1990
DOI: 10.1007/bf00014088
|View full text |Cite
|
Sign up to set email alerts
|

The distribution of benthic invertebrates along a natural turbidity gradient in Lake Temiskaming, Ontario-Quebec

Abstract: Lake Temiskaming, a rift valley lake on the Ontario-Quebec border, exhibits a permanent gradient of turbidity due to tributary streams which cut through clay deposits to the north of the lake. Concentrations of total phosphorus (TP) also decreased from north to south, with values suggesting mesotrophic conditions. Concentrations of chlorophyll a were characteristic of oligotrophic lakes and showed little relationship to either turbidity or TP. Large numbers of Tubificidae were found at our northernmost samplin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
2

Year Published

1996
1996
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 23 publications
2
5
2
Order By: Relevance
“…In agreement with the results of this study, the most common invertebrate taxa observed in the upstream Lake Temiskaming benthic zone (at 10 m depth) included Chironomidae (Procladius, Tanytarsus and Polypedilum), Oligochaeta (Tubifex tubifex) and Hexagenia [36]. Our estimates of invertebrate biomass in Ottawa River sediment (0.1-2.5 g·m -2 ) are considerably lower than those for the Lake Temiskaming reach of the Ottawa River (1.9-17.3 g·m -2 ) [36], likely because we sampled the Ottawa River in November and Lake Temiskaming was sampled in May through August, when pre-emergence biomass is generally at its highest [42,43].…”
Section: Macroinvertebrate Community In Ottawa River Sedimentsupporting
confidence: 91%
See 4 more Smart Citations
“…In agreement with the results of this study, the most common invertebrate taxa observed in the upstream Lake Temiskaming benthic zone (at 10 m depth) included Chironomidae (Procladius, Tanytarsus and Polypedilum), Oligochaeta (Tubifex tubifex) and Hexagenia [36]. Our estimates of invertebrate biomass in Ottawa River sediment (0.1-2.5 g·m -2 ) are considerably lower than those for the Lake Temiskaming reach of the Ottawa River (1.9-17.3 g·m -2 ) [36], likely because we sampled the Ottawa River in November and Lake Temiskaming was sampled in May through August, when pre-emergence biomass is generally at its highest [42,43].…”
Section: Macroinvertebrate Community In Ottawa River Sedimentsupporting
confidence: 91%
“…In the only previous study on the benthic invertebrate distribution in the Ottawa River near CRL, Rigler [15] found that Hexagenia was one of the most abundant benthic invertebrate taxa at depths from < 1-16 m, ranging from 10-20 individuals per m 2 . Hexagenia are also an important component of the Lake Temiskaming benthic community, upstream from Chalk River, ranging from 25-103 individuals·m -2 [36]. In this study, we found Hexagenia densities to be similar, ranging from 0-131 individuals·m -2 .…”
Section: Macroinvertebrate Community In Ottawa River Sedimentsupporting
confidence: 58%
See 3 more Smart Citations